IDENTIFICATION OF MERCURY CONTENT AMONG CHILDREN WITH STUNTING AGED 25 - 59 MONTHS IN THE SMALL-SCALE GOLD MINING AREA OF KRUENG SABEE SUB-DISTRICT, ACEH JAYA REGENCY - Lensoni; Nurdin, Ambia; Yulis, Santri (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2023)
This study investigates the hazardous impact of mercury, classified as a Category B3 heavy metal waste, on human life and the environment. It focuses on the significant contribution of artisanal mining to mercury pollution and its adverse effects on the landscape. In particular, the research examines the health risks posed by mercury exposure to children living in Peri-Urban Artisanal and Small-Scale Gold Mining (PESK) areas, including compromised immune responses and the potential for stunting. Urine samples were collected from participants using purposive sampling in accordance with Minister of Health Regulation No. 43/2013 and analyzed using Atomic Absorption Spectroscopy (AAS). All ten samples exhibited the presence of mercury, with one falling below the 7 μg/L threshold established by Human Biomonitoring (HBM) guidelines. Notably, the study found that 99% of stunted toddlers exceeded the mercury threshold, while only 0.1% remained below it. This research contributes to a deeper understanding of the health and environmental implications associated with mercury contamination.